2021
DOI: 10.3389/fvets.2021.656391
|View full text |Cite
|
Sign up to set email alerts
|

Survey on Colostrum Management by Dairy Farmers in the Netherlands

Abstract: Colostrum feeding is essential for the transfer of passive immunity and health of newborn calves. Information on current colostrum management practices to reduce calf morbidity and mortality is important but lacking for Dutch dairy herds. We therefore conducted a survey to investigate colostrum management strategies on Dutch dairy farms. The survey was specifically focused on the most recently born calf and was returned by 107 respondents (response rate of 13.4%). The mean amount of colostrum fed at first feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The study described calf management practices, estimated differences in disease incidences on Austrian dairy farms depending on the farm structure (small farms ≤ 20 cows versus large farms > 20 cows), and different management practices [18]. Investigations carried out in countries such as the Netherlands [27], Brazil [28], Canada [29], and the USA [30] are only partially comparable to studies conducted in Austria since the farm structure is significantly different. In the aforementioned studies, the average number of cattle per farm is significantly higher, with more than 50 to 100 dairy cows per farm.…”
Section: Introductionmentioning
confidence: 99%
“…The study described calf management practices, estimated differences in disease incidences on Austrian dairy farms depending on the farm structure (small farms ≤ 20 cows versus large farms > 20 cows), and different management practices [18]. Investigations carried out in countries such as the Netherlands [27], Brazil [28], Canada [29], and the USA [30] are only partially comparable to studies conducted in Austria since the farm structure is significantly different. In the aforementioned studies, the average number of cattle per farm is significantly higher, with more than 50 to 100 dairy cows per farm.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, by referring to these recent cases, we avoided socially desirable answers to questions regarding culling reasons. This method was the same as the method employed by Robbers et al (2021) to study colostrum management of Dutch dairy farmers. In addition to the most recently culled cows, we asked about the most and least frequent culling reasons on the farm to detect if the recent events were in line with the general situation.…”
Section: Discussionmentioning
confidence: 99%
“…I limited the social desirability bias of responses by asking about the latest instance such as culling reasons for the most recently culled cow. This strategy was previously employed by Robbers et al (2021). I paired these questions with general questions about the most and least frequent reasons for culling to get the specific as well as the general picture.…”
Section: Datamentioning
confidence: 99%
“…One crucial aspect in calf management is timely provision of adequate amounts of high quality colostrum to provide the young calf with immunologic protection in the first weeks of life (Barrington et al, 2002), which can be at risk when care of new-born calves is not prioritized. On most dairy farms calves are fed colostrum by bottle to guarantee sufficient colostrum intake, although a recent survey among Dutch dairy farmers revealed that 50 % of calves born during nighttime risk delayed colostrum administration (Robbers et al, 2021).…”
Section: Current Calf Rearing Practices and Animal Welfarementioning
confidence: 99%